Neurorehabilitation Technology - Dietz, Volker; Nef, Tobias; Rymer, William Zev (Springer London : Imprint: Springer, 2012)
Neurorehabilitation Technology provides an accessible, practical overview of the all the major areas of development and application in the field. The initial chapters provide a clear, concise explanation of the rationale for robot use and the science behind the technology before proceeding to outline a theoretical framework for robotics in neurorehabilitative therapy. Subsequent chapters provide detailed practical information on state-of-the-art clinical applications of robotic devices, including robotics for locomotion; posture and balance and upper extremity recovery in stroke. The text is illustrated throughout with photographs and schematic diagrams which serve to clarify the information for the reader. This book is a valuable resource for neurologists, biomedical engineers, rehabilitation specialists, physiotherapists and those training in these fields.